In silico locating the immune-reactive segments of Lepidium draba peroxidase and designing a less immune-reactive enzyme derivative. (October 2017) - Fattahian, Yaser; Riahi-Madvar, Ali; Mirzaee, Reza; Asadikaram, Gholamreza; Rahbar, Mohammad Reza
Graphical abstract: Highlights: A novel peroxidase sequence was analyzed bioinformatically. Peroxidase is applicable in antibody-directed enzyme prodrug therapy of cancer. Location of immunogenic and allergenic regions of protein were predicted. A derivative sequence with lower immunogenicity and higher stability was designed. Abstract: Peroxidases have broad applications in industry, environmental as well as pharmaceutical and diagnosis. Recently applicability of peroxidases in cancer therapy was mentioned. In the present study, a horseradish peroxidase homologue from Lepidium draba was subjected to in silico analyzes aiming at identifying and locating immune-reactive regions. A derivative sequence with decreased immunogenicity and increased stability also suggested. The tertiary structure of the enzyme was predicted. The functional and structural importance of residues was annotated as well as the conservatory status of each residue. The immune-dominant regions of protein were predicted with various software. N-terminal 4 residues, NFSHTGL (186–192), PRNGN (210–214), PLVRAYADGTQKFFN (261–275), and last 4 residues in C-terminal were predicted to be the consensus immunogenic segments of L. draba peroxidase. The modifications were applied to wild type sequence in order to mitigate its immune-reactiveness. The modifications were based on predicted energetic status of residues and naturally occurred amino acids in each position of the enzyme sequence, extracted from alignment file of 150 homologous peroxidases. The new enzyme derivative is predicted to be less immune-reactive and more stable. Thus the sequence is better suited to therapeutic applications.